IMPACT OF E-COMMERCE, HEALTHCARE LOGISTICS, AND CONSUMER TRUST ON MEDICAL PRODUCT SALES - Diana Pratiwi; Vip Paramarta; ⁠Farida Yuliaty; Alexandra DeSousa Guterres (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
In the era of growing digitalization, e-commerce plays an important role in the distribution of medical products, making it easier for consumers to access medicines, medical devices, and supplements through online platforms. This study aims to analyze the influence of e-commerce, healthcare logistics, and consumer trust on medical product sales. E-commerce in the healthcare sector offers easy access and competitive pricing, but also faces challenges related to product authenticity, transaction security, and applicable regulations. One of the key factors in the success of online medical product sales is efficient logistics, including supply chain management and safe delivery of products. Consumer trust is also a key aspect, where consumers must feel confident in product quality and online transaction security. The method used in this research is a literature review to analyze findings from various academic sources related to health e-commerce, logistics, and consumer trust factors. The results show that an efficient logistics system and high consumer trust play a major role in the success of e-commerce in the healthcare sector. This research provides important insights for the development of safer and more efficient medical product e-commerce business strategies and policies in the future.